Etične dileme v športni medicini - Tonin, Katarina (Rehabilitacija (Ljubljana), 2017)
Background: The article describes the ethical dilemmas that Slovenian national team sports physicians face in their line of duty. A short survey of recent publications on the topic is also presented. Three most common ethical dilemmas are addressed in detail. Methods: Thirteen Slovenian national team physicians fulfilled a questionnaire about ethical dilemmas which they come across at work. Results: The three commonest ethical dilemmas of Slovene national team physicians are doping (n = 7), return to play after injury (n = 7) and doctor-patient/athlete confidentiality (n = 5). Sixty-one per cent of the team physicians would provide information about doping to the national anti-doping agency and 31 % would not. Thirty-eighty per cent of team physicians would provide information about life-threatening health condition to the team management and 54 % would not. Fifty-four per cent of team physicians would allow the return to play of an injured athlete using analgesic injection therapy for an important match, while none of the physicians would do the same for an unimportant match. Conclusions: There is discrepancy among action of Slovenian sports physicians in case of ethical dilemmas. Our survey exposed the commonest three dilemmas and we offer the answers to those dilemmas.
Keywords: avtonomnost bolnika; doctor-patient confidentiality; ethical issues; ethics; etične dileme; informed consent; informirano soglasje; patient autonomy; Sports Medicine; športna medicina; zaupnost podatkov